Prevalensi Kejadian Infeksi HIV Sebagai Screening Test Deteksi AIDS Dengan Metode Imunokromatografi Pada Komunitas Homoseksual - erawati erawati erawati; Siska Kusumawardani; Leni Anggraini Puspita Sari (State University of Gorontalo, 2023)
Human Immunodeficiency Virus (HIV) is a virus that can cause AIDS by attacking white blood cells, namely Cluster Of Differentiation 4 (CD4) cells so it can damage the human immune system. After several years the number of viruses increases so that the immune system is no longer able to fight the incoming disease. Acquired Immuno Deficiency Syndrome (AIDS) often manifests with various opportunistic infections, malignancies, metabolic disorders and others. Homosexual men have a greater risk of contracting HIV/AIDS than heterosexual men, particularly through risky sexual behavior, namely sex with more than one partner and anal sex. This study aims to determine the presence or absence of HIV antibodies in the Homosexual Community at the Pesantren I Public Health Center, Kediri City. The research design used is descriptive research design with quota sampling technique. In HIV testing using the Immunochromatography method with whoole blood the Homosexual Community of Gay. The principle of the examination is a qualitative test method by looking at the color changes on the test strip. The results of the study of 30 respondents, there were 2 positive results of HIV antibodies with a percentage of 7% and 28 negative results of HIV antibodies with a percentage of 93%. The conclusion of this study is that HIV examination using the immunochromatographic method can be used to detect the presence of HIV antibodies and can be used as a screening test for AIDS detection in the Homosexual Community.